2021
DOI: 10.4103/jmu.jmu_105_20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demographic Factors on Nerve Ultrasound of Healthy Participants in a Multiethnic Asian Population

Abstract: Background: High-resolution nerve ultrasound provides morphological information of peripheral nerves. We aimed to determine the normal ultrasonographic reference values of nerve cross-sectional area (CSA) in multiethnic Malaysian healthy participants. Methods: Nerve ultrasound of the median, ulnar, radial, tibial, fibular, and sural nerves was performed in 84 healthy participants at anatomical-defined locations. The CSA at each scanned site was measured by tracing circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
4
16
1
Order By: Relevance
“…Only eight studies (11.4%) included any information regarding participant race/ethnicity, but it is becoming increasingly evident this may affect peripheral nerve size. 13 In addition, although sex and age are known to affect peripheral nerve size, only one study stratified nerve measurements based on these parameters, thus limiting our ability to correct for sex or age in the meta-analysis. Furthermore, although tracing within the hyperechoic epineural rim is the most commonly used method for determining the sonographic CSA of nerves, two studies did not do so, 35,79 and nine others omitted CSA technique information entirely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only eight studies (11.4%) included any information regarding participant race/ethnicity, but it is becoming increasingly evident this may affect peripheral nerve size. 13 In addition, although sex and age are known to affect peripheral nerve size, only one study stratified nerve measurements based on these parameters, thus limiting our ability to correct for sex or age in the meta-analysis. Furthermore, although tracing within the hyperechoic epineural rim is the most commonly used method for determining the sonographic CSA of nerves, two studies did not do so, 35,79 and nine others omitted CSA technique information entirely.…”
Section: Discussionmentioning
confidence: 99%
“…10 Normal, healthy nerve size is known to vary with a number of factors, including anatomical location, sex, 11 body size, 12 age, 12 and race/ethnicity. 13 Sonographic measures of nerve size are also operator-dependent. 8 In addition to this known variability, changes in nerve size are seen across a range of peripheral nerve disorders, including compressive neuropathies, trauma, neuroma, and generalized neuropathies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study 33 showed that the CSA of the median nerve at the wrist was smaller in the Indian participants than the Dutch participants. Another study 34 showed that nerve CSA in Malay participants was larger than in Chinese and Indian participants. The most conservative approach is for each laboratory to determine their own reference values.…”
Section: Influence Of Demographic Variablesmentioning
confidence: 96%
“…9 Reference nerve ultrasound data were derived from established values from our laboratory. 18 The study was approved by the UMMC research ethics committee and all patients provided informed consent.…”
Section: Gbs Patients Admitted To University Of Malayamentioning
confidence: 99%